2018
DOI: 10.14814/phy2.13612
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cardiomyocyte function by in vivo hexarelin treatment in streptozotocin-induced diabetic rats

Abstract: Diabetic cardiomyopathy is characterized by diastolic and systolic cardiac dysfunction, yet no therapeutic drug to specifically treat it. Hexarelin has been demonstrated to improve heart function in various types of cardiomyopathy via its receptor GHS‐R. This experiment aims to test the effect of hexarelin on cardiomyocytes under experimental diabetes. Streptozotocin (STZ, 65 mg/kg)‐induced diabetic rat model was employed with vehicle injection group as control. Daily hexarelin (100 μg/kg) treatment was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Consistent with such a GH-independent role, peripheral ghrelin actions have been linked to clinical implications of cardiovascular disease, insulin resistance, and obesity [ 31 , 56 , 57 , 58 , 59 ]. Likewise, GH-independent effects on fat metabolism, cardioprotection, hemodynamic control, and bone cell differentiation have been reported for GHRPs [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Hence, such peripheral effects of GHRPs are thought to play important roles in energy homeostasis, adiposity and vascular integrity and identify the GHRPs as highly promising therapeutic targets in metabolic diseases.…”
Section: Central Vs Peripheral Actions Of Ghrpsmentioning
confidence: 97%
“…Consistent with such a GH-independent role, peripheral ghrelin actions have been linked to clinical implications of cardiovascular disease, insulin resistance, and obesity [ 31 , 56 , 57 , 58 , 59 ]. Likewise, GH-independent effects on fat metabolism, cardioprotection, hemodynamic control, and bone cell differentiation have been reported for GHRPs [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Hence, such peripheral effects of GHRPs are thought to play important roles in energy homeostasis, adiposity and vascular integrity and identify the GHRPs as highly promising therapeutic targets in metabolic diseases.…”
Section: Central Vs Peripheral Actions Of Ghrpsmentioning
confidence: 97%
“…There are also changes in myocardial GHSR1a levels and messenger RNA in congestive heart failure in humans. 8 We 8 and others 34 have shown that myocardial GHSR1a decreases during the progression of diabetic cardiomyopathy, with a negative correlation between GHSR1a and development of impaired glucose tolerance. 8 Therefore, GHSR1a may be a biomarker for cardiomyopathies or heart failure, and developing radioligand-based imaging agents that target GHSR1a may complement existing imaging modalities in the detection of changes in heart function that may indicate onset of heart disease or heart failure.…”
Section: Discussionmentioning
confidence: 86%